That’s the Way we do Things Around Here: Achieving the Company’s Innovation Through Organizational Innovation Culture - Arsanti, Tutuk (Indonesian Journal Publisher, 2025)
This paper aims to gain an understanding of the role of organizational innovation culture in achieving a company’s innovation. The inability to understand how the role of organizational culture can lead to problems such as unproductive behavior, the failure of innovation, and a reluctance to collaborate. Therefore, building an organizational innovation culture is crucial to achieving a company’s innovation. Attention is directed to the determining factors that must be considered to strengthen the company’s innovation culture. The content of the paper primarily draws on observations and in-depth interviews with top leaders and other organizational members. These individuals embody both the organizations and the personnel engaged in innovation activities, as well as participating in efforts to cultivate organizational culture. The findings indicate that fostering a culture of organizational innovation through the development of family-like connections, cooperation, and mentorship can create a supportive work environment that encourages the generation of innovative ideas. Furthermore, cultivating both the infrastructure for innovation and a commitment to innovation is essential for advancing an organizational culture that prioritizes innovation. Ultimately, these efforts can significantly influence the achievement of various innovations within the company. This research highlights the necessity of adopting a managerial approach that actively fosters a culture of innovation within the company. By doing so, organizations can create an environment that not only supports but also inspires creative thinking and innovation.